2014
DOI: 10.1007/s10681-014-1301-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of mixed models for evaluating stability and adaptability of maize using unbalanced data

Abstract: The aim of this study was to use a multienvironment trial approach from a mixed model point of view for factor analysis (FA) of the stability and adaptability of hybrids. Twenty-eight hybrids were analyzed in 35 environments across four seasons/years (summer season 2010, winter season 2011, summer season 2011 and winter season 2012). Several of these hybrids were analyzed during the first seasons and were not evaluated in later seasons or vice versa. Therefore, the dataset used in this study simulated the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
3
11
0
1
Order By: Relevance
“…This is even more interesting when considering the situation of plant breeding programs in general, in which unbalanced data are common, as in the case of this study, which considers a series of data from VCU trials, set up over a series of years, in which better performing hybrids are retained for at least 2 years and the others substituted by new hybrids. Figueiredo et al (2014) also found that the AF methodology can safely be used in studies of adaptability and stability in trials with a high degree of unbalanced data. Moreover, we can highlight the study of Smith et al (2015) who emphasized the superiority of this methodology for evaluation of trials in multi-environments over several years.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is even more interesting when considering the situation of plant breeding programs in general, in which unbalanced data are common, as in the case of this study, which considers a series of data from VCU trials, set up over a series of years, in which better performing hybrids are retained for at least 2 years and the others substituted by new hybrids. Figueiredo et al (2014) also found that the AF methodology can safely be used in studies of adaptability and stability in trials with a high degree of unbalanced data. Moreover, we can highlight the study of Smith et al (2015) who emphasized the superiority of this methodology for evaluation of trials in multi-environments over several years.…”
Section: Resultsmentioning
confidence: 95%
“…In the same context, Smith et al (2001) proposed a general class of analytic factor (AF) models that encompassed the approach of Piepho (1998) and included spatial errors for each trial based on Figueiredo et al (2014). In this way, the authors sought to develop models that could provide considerations by data from various evaluation environments.…”
Section: Introductionmentioning
confidence: 99%
“…While environments were considered as fixed effects in these analyses, replicates within environments, hybrids and hybrid by environment interaction were regarded as random effects (Piepho, 1998;Smith et al, 2001). This approach has proven to be effective in generating biplots which graphically represent genotype stability and adaptability in MET (Burgueño et al, 2008;Crossa et al, 2010;Crossa et al, 2013;Figueiredo et al, 2015). The two factor analysis (FA(2)) that has become a standard model for MET analysis (Kelly et al, 2007) was used in the analyses of all data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Corn cultivation occurs practically throughout the country and production occurs at different periods of the year (agricultural crops) depending on the region (IBGE, 2015). The first crop or summer crop is grown mainly between September and March, while the second harvest in the off or "second" season is grown mostly between the months of January and May (Figueiredo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The edaphoclimatic conditions of cultivation in the off season and summer vary considerably, but the vast majority of cultivars planted in the first harvest are also recommended for off season since corn breeding programs for off season are newer and less developed than those for summer corn breeding programs, and many cultivars from the breeding programs of the summer harvest show good performance and adaptation in the off season (Figueiredo et al, 2014). According to Fritsche-Neto et al (2010) the success of a cultivar in the market is associated with high productive performance and the agronomic characteristics.…”
Section: Introductionmentioning
confidence: 99%